NT5E upregulation in head and neck squamous cell carcinoma: A novel biomarker on cancer-associated fibroblasts for predicting immunosuppressive tumor microenvironment - Chen, Xue-min; Liu, Yu-yang; Tao, Bing-yan; Xue, Xin-miao; Zhang, Xin-xin; Wang, Lin-lin; Zhong, Hui; Zhang, Jun; Yang, Shi-ming; Jiang, Qing-qing (Frontiers in Immunology, 2022)
Despite tremendous progress made in the diagnosis and managements, head and neck squamous cell carcinoma (HNSC) remains a global medical dilemma with dismal clinical prognosis and high mortality. Gene NT5E encodes the ecto-5’-nucleotidase (CD73), which facilitates the formation of immunosuppressive tumor microenvironment (TME) permissive for tumor progression in various malignancies. Nevertheless, the cell subsets NT5E expressed on and the potential function of NT5E in the TME of HNSC remain virgin lands in HNSC. In this study, we comprehensively performed integrated prognostic analysis and elucidated that NT5E was an independent prognostic indicator for HNSC, for which a high NT5E level predicted poor overall survival (OS), disease-specific survival (DSS) and progression-free interval (PFI) in HNSC patients (p<0.05). Enrichment analyses revealed the close correlation between NT5E and ECM remodeling, and the latent function of NT5E may involve in epithelial-to-mesenchymal transition (EMT) and metastasis during HNSC progression. HNSC-related immune infiltration analysis and single-cell type analysis demonstrated that NT5E expression was significantly positively associated with cancer-associated fibroblasts (CAFs) in HNSC (p<0.01). NT5E-related TME analysis revealed that NT5E-high group are characterized by low neoantigen loads (NAL, p<0.001) and tumor mutation burden (TMB, p<0.01), indicating high-NT5E-expression HNSC patients may be recalcitrant to immunotherapy. In-situ multicolor immunofluorescence staining was later conducted and the results further verified our findings. Taken together, NT5E could be a novel biomarker in HNSC. Predominantly expressed on CAFs, the upregulation of NT5E might predict an immunosuppressive TME for HNSC patients who may benefit little from immunotherapy. Targeting CAFs with high NT5E expression might be a novel therapeutic strategy for HNSC patients.